Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian di Apotek Parviz Kota Palangka Raya - Handayani, Rezqi; Anggriani Pramudita; Fauzia, Husna (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Pharmaceutical services involve direct and responsible care for patients related to pharmaceutical preparations, aiming to achieve definite results that enhance patients' quality of life. One indicator of healthcare quality is measuring user satisfaction. Apotek Parviz provides pharmaceutical services to the surrounding community, offering dual healthcare services—doctor diagnosis and pharmaceutical care—thus improving the health and quality of life for residents of Palangka Raya City. This study aims to determine patient satisfaction levels with pharmaceutical services at Apotek Parviz in Palangka Raya City, based on five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. This descriptive study used a questionnaire with a sample size of 86 respondents selected through accidental sampling. The research results showed that the satisfaction percentages for each dimension were: 87.43% for tangibility, 81.16% for reliability, 83.25% for responsiveness, 84.49% for assurance, and 83.25% for empathy. The overall average satisfaction across the five dimensions, according to the Likert scale, was 84.18%, indicating that patients are very satisfied with the pharmaceutical services at Apotek Parviz in Palangka Raya City.